Substantial numerical decline in South Australian rabbit populations following the detection of rabbit haemorrhagic disease virus 2. (19th May 2018) - Mutze, Greg; De Preu, Nicki; Mooney, Trish; Koerner, Dylan; McKenzie, Darren; Sinclair, Ron; Kovaliskli, John; Peacock, David
Abstract : Lagovirus europaeus GI.2, also commonly known as rabbit haemorrhagic disease virus 2, was first detected at two long‐term monitoring sites for European rabbits, Oryctolagus cuniculus, in South Australia, in mid‐2016. Numbers of rabbits in the following 12–18 months were reduced to approximately 20 per cent of average numbers in the preceding 10 years. The impact recorded at the two South Australian sites, if widespread in Australia and persistent for several years, is likely to be of enormous economic and environmental benefit.